Cancer risk in primary biliary cirrhosis: a study in northern England. Issue 5 (1st November 1999) - Howel, D; Metcalf, J V; Gray, J; Newman, W L; Jones, D E J; James, O F W
Abstract : BACKGROUND: Suggestions that breast cancer may be more common in patients with primary biliary cirrhosis (PBC) have been challenged. It has recently been proposed that total cancer rates may be higher in patients with PBC, as well as liver cancers. AIMS: To investigate these proposals on a strictly defined case series. SUBJECTS: A total of 769 prevalent or incident PBC patients with "definite" or "probable" disease detected in a defined area of the north-east of England during 1987–94. METHODS: Cancer events and deaths were identified by obtaining information from one or more of the following sources: Office for National Statistics (ONS) Central Registers, Regional Cancer Registry, and clinical case records. Standardised cancer incidence (SIR) and mortality ratios (SMR) were calculated using the local region as the standard population. RESULTS: There were 97 cancer events during 1987–96. SIR from cancer registrations for all cancers was 1.7 (95% confidence interval (CI) 1.3 to 2.2), for liver cancer was 74 (95% CI 32 to 146), and for breast cancer was 1.1 (95% CI 0.4 to 2.4). SMR for all cancers was 1.8 (95% CI 1.4 to 2.4), for liver cancer was 39 (95% CI 20 to 68), and for breast cancer was 0.4 (95% 0.1 to 1.6). The results were similar after excluding the first year of follow up after PBC diagnosis. CONCLUSIONS: There was some evidence of a small increase in overall cancer incidence and mortality in PBC patients. With the exception of liver cancer, it is unlikely that there is a high excess incidence for PBC patients from any cancer at a particular site, and specifically breast cancer.